The adenosine monophosphate–activated protein kinase—vacuolar adenosine triphosphatase–pH axis: A key regulator of the profibrogenic phenotype of human hepatic stellate cells. Issue 3 (16th July 2018) - Marrone, Giusi; De Chiara, Francesco; Böttcher, Katrin; Levi, Ana; Dhar, Dipok; Longato, Lisa; Mazza, Giuseppe; Zhang, Zhenzhen; Marrali, Martina; Fernández‐Iglesias, Anabel; Hall, Andrew; Luong, Tu Vinh; et al.
Abstract : Liver fibrosis and cirrhosis are characterized by activation of hepatic stellate cells (HSCs), which is associated with higher intracellular pH (pHi). The vacuolar H + adenosine‐triphosphatase (v‐ATPase) multisubunit complex is a key regulator of pHi homeostasis. The present work investigated the functional role of v‐ATPase in primary human HSC (hHSC) activation and its modulation by specific adenosine monophosphate–activated protein kinase (AMPK) subunits. We demonstrate that the expression of different v‐ATPase subunits was increased in in vivo and in vitro activated hHSCs compared to nonactivated hHSCs. Specific inhibition of v‐ATPase with bafilomycin and KM91104 induced a down‐regulation of the HSC fibrogenic gene profile, which coincided with increased lysosomal pH, decreased pHi, activation of AMPK, reduced proliferation, and lower metabolic activity. Similarly, pharmacological activation of AMPK by treatment with diflunisal, A769662, and ZLN024 reduced the expression of v‐ATPase subunits and profibrogenic markers. v‐ATPase expression was differently regulated by the AMPK α1 subunit (AMPKα1) and AMPKα2, as demonstrated in mouse embryo fibroblasts specifically deficient for AMPK α subunits. In addition, activation of v‐ATPase in hHSCs was shown to be AMPKα1‐dependent. Accordingly, pharmacological activation of AMPK in AMPKα1‐depleted hHSCs prevented v‐ATPase down‐regulation. Finally, we showed that v‐ATPase expression was increased in fibrotic livers from bile duct–ligated mice and in human cirrhotic livers. Conclusion: The down‐regulation of v‐ATPase might represent a promising target for the development of antifibrotic strategies. (Hepatology 2018).